Modern advancements in continuous-flow aided kinetic analysis. Issue 5 (18th February 2022) - Taylor, Connor J.; Manson, Jamie A.; Clemens, Graeme; Taylor, Brian A.; Chamberlain, Thomas W.; Bourne, Richard A.
Abstract : Although kinetic analysis has traditionally been conducted in a batch vessel, continuous-flow aided kinetic analysis continues to swell in popularity. Abstract : Although kinetic analysis has traditionally been conducted in a batch vessel, continuous-flow aided kinetic analysis continues to swell in popularity. This can be partly attributed to the favourable characteristics of flow reactors and the growth of flow chemistry in general. However, the development of innovative techniques in recent years to obtain more kinetic information using less reaction material, has further accelerated its adoption. These advancements allow faster and more efficient routes to total process understanding, thereby allowing optimum reaction conditions to be identified in process development to maximise product outputs. This minireview documents novel methodologies reported in the recent literature, both to highlight opportunities for their exploitation and to enable further adoption of kinetic analysis in continuous-flow systems in years to come.